(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The novel World and Town by Gish Jen explores the challenges of cultural assimilation in a panoramic way.Gish Jen is a contemporary American writer and speaker of Chinese descent. Jen raises thought-provoking questions about the complexities of personal and communal identity and the impact of immigration and globalization on a community through her novel. The paper discusses the clash of traditions and values experienced by new cultural norms, the erosion of community values and traditions with the influx of new cultures, the frustration and tension in intercultural interactions, the difficulty in balancing cultural heritage and assimilation, and the generational gap in attitudes towards assimilation. It also highlights the costs of assimilation on personal identity. The abstract concludes by emphasizing the importance of inclusive and empowering approaches toassimilation in order to foster social cohesion.